2016
DOI: 10.17352/2455-2968.000022
|View full text |Cite
|
Sign up to set email alerts
|

High-Voltage Electrically Head Injury Presenting underlying Calvarial Osteomyelitis: Single Indonesian Tertiary Hospital Experience

Abstract: Objective: To demonstrate the characteristic of high-voltage electrically head injury patients presenting underlying calvarial osteomyelitis. Methods: Retrospectively report of patients high-voltage electrically head injured with calvarial osteomyelitis from January 1 st 2011 to December 31 st 2013. The demographic variable namely age, sex, place of accident, present of calvarial osteomyelitis, Glasgow coma scale, surgical treatment type, grading of burn injury and total body surface area of burn (TBSA). Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In a sense, chronic OM of the skull by high-voltage electrical burn on the scalp is inevitable, because complete and perfect debridement of the necrotic skull bone is practically impossible at the time of flap coverage, as previously described. Another study also reported that all patients suffered from calvarial osteomyelitis during treatments of high-voltage electrical burns on the scalp in 11 patients [1]. They reported that it was difficult to treat calvarial osteomyelitis due to a high relapse risk.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a sense, chronic OM of the skull by high-voltage electrical burn on the scalp is inevitable, because complete and perfect debridement of the necrotic skull bone is practically impossible at the time of flap coverage, as previously described. Another study also reported that all patients suffered from calvarial osteomyelitis during treatments of high-voltage electrical burns on the scalp in 11 patients [1]. They reported that it was difficult to treat calvarial osteomyelitis due to a high relapse risk.…”
Section: Discussionmentioning
confidence: 99%
“…Complete debridement of necrotic tissue and bone with appropriate antibiotics is necessary [1]. If previous coverage was with a skin graft, flap coverage is desirable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The upper limb has been reported as the most common entry point for electrical injury [ [8] , [9] , [10] ]. However, the scalp has also been reported as a common entry point for electrical injury, though less frequently than the upper limb [ 5 , 11 ]. Our patient had an entry point on the right elbow and an exit point on the lateral aspect of the right thigh.…”
Section: Discussionmentioning
confidence: 99%